2023
DOI: 10.1007/s00227-023-04189-1
|View full text |Cite
|
Sign up to set email alerts
|

Growth rates and age at maturity of Mediterranean loggerhead sea turtles estimated from a single-population foraging ground

Abstract: In sea turtles, somatic growth rates and Age at Sexual Maturity (ASM) are important parameters for investigating population dynamics. Moreover, ASM informs on the time lag needed to observe the effects of past environmental variables, threats and conservation measures acting at nesting beaches on future numbers of clutches or nesting females, that are the most monitored indices. Assessing ASM of mixed populations that share the same foraging areas is difficult, as in the case of the Mediterranean Sea that is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 75 publications
0
4
0
1
Order By: Relevance
“…Adult loggerheads are omnivores and known as bioturbators of marine sediments during their foraging behaviour and thus increase the chances of new cyanobacteria colonisation on their carapace (Lazar et al 2011). Recent studies (Baldi et al 2023, Mariani et al 2023) have indicated that in the Mediterranean loggerhead population, the distinction between the oceanic and neritic phases is less pronounced, primarily because of easily accessible shallow foraging grounds, particularly in the Adriatic Sea (Casale et al 2008). Nevertheless, our results reveal clear differences in cyanobacterial communities between adults and juveniles, reflecting certain aspects of turtle biology and ecology.…”
Section: Discussionmentioning
confidence: 99%
“…Adult loggerheads are omnivores and known as bioturbators of marine sediments during their foraging behaviour and thus increase the chances of new cyanobacteria colonisation on their carapace (Lazar et al 2011). Recent studies (Baldi et al 2023, Mariani et al 2023) have indicated that in the Mediterranean loggerhead population, the distinction between the oceanic and neritic phases is less pronounced, primarily because of easily accessible shallow foraging grounds, particularly in the Adriatic Sea (Casale et al 2008). Nevertheless, our results reveal clear differences in cyanobacterial communities between adults and juveniles, reflecting certain aspects of turtle biology and ecology.…”
Section: Discussionmentioning
confidence: 99%
“…Pencemaran sampah laut Menurut Undang-Undang Nomor 27 Tahun 2007, disebutkan bahwa Konservasi Wilayah Pesisir dan Pulau-Pulau Kecil yaitu upaya perlindungan, pelestarian, dan pemanfaatan wilayah Pesisir dan Pulau-Pulau Kecil serta ekosistemnya untuk menjamin keberadaan, ketersediaan, dan kesinambungan Sumber Daya Pesisir dan Pulau-Pulau Kecil dengan tetap memelihara dan meningkatkan kualitas nilai dan keanekaragamannya. Selama ini, kegiatan konservasi penyu dihadapkan dengan beberapa tantangan, antara lain pertumbuhan yang lambat dan tingkat maturity yang lama, membutuhkan waktu antara 15 dan 50 tahun untuk mencapai kematangan reproduksi tergantung spesies (Colman et al, 2015;Baldi et al, 2023), tingginya angka kematian pada penyu muda dan penyu sebagai hasil tangkapan sampingan (by-catch) (Reimer et al, 2023;WWF-Indonesia, 2017), sebaran penyu, migrasi yang lama antara feeding ground dan nesting area, kebiasaan bertelur di satu lokasi, dan ketergantungan pada suhu di penangkaran (Pike, 2013;Elfidasari et al, 2022). Berbagai peraturan telah ditetapkan untuk melindungi penyu baik berdasarkan ketentuan hukum nasional maupun internasional, karena populasinya semakin menurun akibat faktor alam maupun manusia.…”
Section: Hasil Dan Pembahasanunclassified
“…We converted the substitutions value from (site × million year) −1 to (site × generation) −1 , where the generation time is calculated as age of maturity plus half of reproductive longevity (Pianka 1973). We used 25 years as age of maturity and 22 years as reproductive longevity which resulted in a 36-year generation time (Margaritoulis et al 2020;Baldi et al 2023). We set a normal distribution (mean = 1.2E-7, S.D.…”
Section: Mitogenomic Diversity and Phylogenetic Analysismentioning
confidence: 99%